Analysis of the structure of energy sources (solid fuel, natural gas) in individual low-rise buildings planned for construction in the Republic of Sakha (Yakutia) - Shvetsova Svetlana (E3S Web of Conferences, 2023)
This article analyzes the structure of energy sources (solid fuel, natural gas) in individual low-rise buildings planned for construction in the Republic of Sakha (Yakutia). The indicators for the number of houses intended for heating with solid fuel (coal) and the number of houses intended for heating with natural gas have been clarified. Differences in different age groups of future homeowners are taken into account. The results confirm the preference for natural gas as an energy source in the new individual houses planned for construction in the Republic of Sakha (Yakutia). These studies can be used in the development of development programs in the relevant area.